13 and 3/4 - Greenwald, Lisa (Greenwald, Lisa. Friendship list novel., 2020)
"Ari and Kaylan aren't sure how they're going to survive their first summer apart. No pool. No sleepovers. No emergency late night chats on the porch. So as Ari returns to Camp Silver and Kaylan heads off to comedy camp, they come up with a new list of 13 and 3/4 ways to keep their friendship strong as they tackle everything from bias to batik and moping to matchmaking"--